Epac signaling is required for hippocampus-dependent memory retrieval - Ouyang, Ming (National Academy of Sciences, 2008)
Previously we uncovered a critical role for norepinephrine and β(1)-adrenergic signaling in hippocampus-dependent memory retrieval. Because the β(1) receptor couples to G(s), we examine here whether cAMP is also required for contextual memory retrieval. Using pharmacologic and genetic approaches to manipulate cAMP and downstream signaling, we demonstrate that cAMP and two of its targets, protein kinase A (PKA) and exchange protein activated by cAMP (Epac), are both required for retrieval. These findings demonstrate that cAMP signaling through Epac (as well as PKA) plays an essential role in cognition.